2000
DOI: 10.1021/jp994308s
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Study of Polyatomic Clusters of AlN, GaN, and InN. 1. Structure, Stability, Vibrations, and Ionization

Abstract: In this paper we study the chemical bonding of the small (monomer, triatomic, and dimer) neutral clusters of AlN, GaN, and InN presented earlier in paper 1. It includes the analysis of the topology of the electron density and its Laplacian, together with relevant atomic properties, in light of the theory of atoms in molecules. The most prominent feature of the bonding here, the existence of strong N-N bonds, is seen to diminish with an increase in the number of metal atoms and the degree of ionicity. The Al-N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
105
8
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 19 publications
18
105
8
1
Order By: Relevance
“…2 Representing a link between the isolated molecular world and the solid state, the study of these clusters with different sizes has drawn increasing attention during the last few years; this attention was mainly focused on Al x N y . [3][4][5][6][7][8][9][10][11][12] A few studies were also carried out on Ga x N y and In x N y . [8][9][10][11]13 Recent experimental studies on gaseous AlN using infrared spectroscopy and the Knudsen cell mass showed the existence of a large diversity of neutral and charged species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Representing a link between the isolated molecular world and the solid state, the study of these clusters with different sizes has drawn increasing attention during the last few years; this attention was mainly focused on Al x N y . [3][4][5][6][7][8][9][10][11][12] A few studies were also carried out on Ga x N y and In x N y . [8][9][10][11]13 Recent experimental studies on gaseous AlN using infrared spectroscopy and the Knudsen cell mass showed the existence of a large diversity of neutral and charged species.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] A few studies were also carried out on Ga x N y and In x N y . [8][9][10][11]13 Recent experimental studies on gaseous AlN using infrared spectroscopy and the Knudsen cell mass showed the existence of a large diversity of neutral and charged species. 7,14,15 In addition, photoelectron spectroscopy experiments [16][17][18][19] and their theoretical analysis [20][21][22] were reported for Al x P y , Ga x P y , and In x P y .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GaAs clusters have been modeled by various groups including Chelikowsky and coworkers (15,16) and others (17)(18)(19)(20)(21)(22)(23)(24)(25). GaN clusters have also been studied by Pandey and coworkers (26)(27)(28) as well as others (29)(30)(31)(32). AlP has also been studied by a number of investigators (33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…Numerous derivatives of these oligomers (in which the H atoms are replaced by organic groups) were synthesised and structurally characterised with the help of X-ray diffraction. [7] Quantumchemical calculations on the reaction energies and structures of these oligomers in the light of possible CVD processes have especially been carried out by Thimoshkin et al [8][9][10] [11,12] Thus it is unlikely that solid AlN or GaN is formed via these molecules. In addition, the formal dimers Al 2 N 2 and Ga 2 N 2 were calculated to be essentially weak complexes of the metal atoms or dimers to dinitrogen.…”
Section: Introductionmentioning
confidence: 99%